The feasibility and efficiency for constructing arteriovenous fistula with <2 mm vein—a systematic review and meta-analysis - Feng, Ruijia; Wang, Siwen; Yu, Jianwen; Zheng, Xunhua; Chen, Wei; Wang, Xin; Chang, Guangqi (Frontiers in Cardiovascular Medicine, 2023)
Background Autogenous arteriovenous fistula (AVF) is an efficient hemodialysis access for patients with end-stage kidney disease (ESKD). The specific threshold of vein diameter still not reached a consensus. Method We conducted a comprehensive search in PubMed, Embase, and Web of Science databases for articles which comparing the treatment outcomes of AVF with 2 mm as vein diameter threshold. Fixed and random effect model were used for synthesis of results. Subgroup analysis was designed to assess the risk of bias. Result Eight high-quality articles were included finally. Among a total of 1,075 patients (675 males and 400 females), 227 and 809 patients possessed <2 mm and ≥2 mm vein respectively. Apart from gender and coronary artery disease (P < 0.05), there was no significant difference in age, diabetes, hypertension or radial artery between maturation and non-maturation groups. The functional maturation rate was lower in patients with <2 mm vein according to fixed effect model [OR = 0.19, 95% CI (0.12, 0.30), P < 0.01]. There was no significant difference in primary [OR = 0.63, 95% CI (0.12, 3.25), P = 0.58] or cumulative patency rates [OR = 0.40, 95% CI (0.13, 1.19), P = 0.10]. Conclusion Vein diameter less than 2 mm has a negative impact on the functional maturation rate of AVF, while it does not affect the primary and cumulative patency rates (12 months).